Psychology of social inertia in the sphere of physical recreation and conditions for its overcoming - Elmurzaev M.A. ,; Agayev R.A. ,; Novikova A.V. ,; Yakovlev S.A. ,; Zakharov A.E. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the psychological mechanisms of the emergence of social inertia in the field of physical recreation and ways to overcome it. Methods and structure of the study. The methodological basis of the study was based on empirical and interdisciplinary approaches, based on theoretical analysis and generalization of the literature. Results and conclusions. Objective and subjective reasons for the social inertia of individuals in relation to their health and manifestations of social activity contribute to the emergence of a state of deprivation associated with a biologically complete, but psychologically insufficient living environment, which leads to a violation of the overall state of health. The development of ways to overcome the psychology of social inertia should include, first of all, the restructuring of the mass consciousness of people, their traditional way of life, traditions and habits.